Consumer willingness to pay for domestic water services in Kelantan - Kamaludin, Mahirah (2012)
The importance of woter to life connot be denied ond it Is the most precious substance among all of our notural resources. High rapid population growth and urbonization have increased the demond for water which is expected to undergo substantial changes in the future. Kelontan faces many problems in the water sector. The state lacks financial sources in order to improve its water supply coverage. There are numerous functions which will support by water price itself in the industry and it requires in delivering a clean ond adequate supply to water top. Cheap water rates may threoten heavy losses to the water provider who is expected to provide various services to the community. This study utilizes Contingent Voluation Method (CVM) in order to derive consumers' willingness to pay (WTP) for improved water services; and based on the WTP value obtoined, the aggregate monetary benefits of improving water services for the consumers of Kelontan will be estimated. The estimated meon WTP for improved domestic water services is RMO.596 applies on first 35m3 (i.e. 8.36% above the current price). The findings offer policy recommendations to they address the numerous, serious water issues facing the state. The appropriate woter toriff may help water provider to overcome the problems in providing better services in the state.